CLASSIFICATION OF INDICATORS OF THE BUDGET SYSTEM AND TREASURY PERFORMANCE IN THE COUNTRY - Mamayusupova Shakhina Ulugbek kizi; Mirdjamalov Daler; Abdullaev Asrorjon (American Journals, 2023)
Each country has its own budget system and it has a financial policy. And here is the financial state budget system showing the mutual proportionality of state expenses and incomes for security will give. In addition, the annual national budget is a systematic financial document is the main factor that determines the purpose of poverty. Also, the income of the country's local budget funds and budget funds that achieve cost proportionality and others. Balance provides for an increase in the quality and rationality of distribution. Funds of budgets of the budget system effective and rational spending control over state finances further development of the control system, specific target directions of budget funds regulation of spending, the main priorities of the budget policy is considered.
Keywords: Finance, treasury, system, GDP, analyse, income, outcome, position, department, innovative, strategic.